Pengaruh Iklan YouTube Lazada “Pengiriman Cepat Gratis Ongkir” Terhadap Brand Awareness Pada Gen Z di Bogor - Dea Arneta Setyovani; Rizky Fauzi (Jurnal Riset Multidisiplin Edukasi, 2025)
The growth of e-commerce users in Indonesia continues to increase, reaching 196.47 million people in 2023 with a 9.8% increase from the previous year. It is predicted that the number of users will reach 208.55 million by the end of 2024. The impact of the rapid growth of e-commerce in Indonesia has triggered intensified business competition among companies in the sector, prompting them to strengthen their brands through advertising strategies, including through the YouTube platform. As one of the e-commerce companies in Indonesia, Lazada has been using the YouTube platform to promote its brand. One of Lazada's ads featuring Isyana Sarasvati with the message “Fast Delivery Free Shipping” has caught the attention of many people, with over 319 million views. This study aims to determine the influence and how much influence Lazada's YouTube ad “Fast Delivery Free Shipping” has on brand awareness among Gen Z in Bogor. This study uses a quantitative method with non-probability sampling with Convenience Sampling technique distributed to 100 respondents, where questionnaire fillers with the criteria are YouTube user respondents, exposed to Lazada “Fast Delivery Free Shipping” advertisements, generation Z with ages 18-26 years, and domiciled in Bogor. The results of this study indicate that Lazada's YouTube ad “Fast Delivery Free Shipping” has an influence on Brand Awareness in the category of brand recognition among generation Z in Bogor.